2016
DOI: 10.1126/science.aaf1652
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comment on “Cycling Li-O 2 batteries via LiOH formation and decomposition”

Abstract: We described a lithium-oxygen (Li-O 2 ) battery comprising a graphene electrode, a dimethoxyethane-based electrolyte, and H 2 O and lithium iodide (LiI) additives, lithium hydroxide (LiOH) being the predominant discharge product. We demonstrate, in contrast to the work of Shen et al., that the chemical reactivity between LiOH and the triiodide ion (I 3 -) to form IO 3 -indicates that LiOH can be removed on charging; the electrodes do not clog, even after multiple cycles, confirming that solid products are reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 8 publications
2
27
0
Order By: Relevance
“…Recently, Liu et al. have shown that the reaction between LiOH and I 3 − can result in the formation of LiIO or LiIO 3 …”
Section: Figuresupporting
confidence: 77%
“…Recently, Liu et al. have shown that the reaction between LiOH and I 3 − can result in the formation of LiIO or LiIO 3 …”
Section: Figuresupporting
confidence: 77%
“…18,47,48 Similarly, Zhu et al 48 to form iodine (I 2 ), 53 where the potentials of the I À /I 3 À and I 3 À /I 2 redox transitions can be significantly influenced by solvent. [52][53][54] While it has been previously suggested that changes in these redox potentials may be important for the performance of LiI as a redox mediator in Li-O 2 batteries, 26,52 this effect has not been studied systematically.…”
Section: Context and Scalementioning
confidence: 99%
“…For instance, water and protons were found in one study to significantly influence the crystal growth of Li 2 O 2 (refs 20 , 21 ). In other studies, lithium hydroxide (LiOH) was however identified as the main discharge product in the presence of moisture 15 16 , whereas disputes persist on the oxidation of LiOH by triiodide (I 3 − ) during charging process 22 23 24 25 26 27 . Moreover, water was believed to catalyse the ORR reaction in aprotic Li-O 2 battery resulting in the formation of LiOH 28 , and good cycling performance was achieved in humid O 2 (ref.…”
mentioning
confidence: 99%